2019
DOI: 10.29238/teknolabjournal.v8i2.189
|View full text |Cite
|
Sign up to set email alerts
|

Total Lymfosit Count (TLC) with CD4 in HIV/AIDS Patients at Kupang

Abstract: Human Immunodeficiency Virus (HIV) is a retrovirus originating from the retroviridae family of the genus lentivirus that infects and damages cells that have a molecule Cluster of Differentiation 4 (CD4), especially T lymphocytes that have receptors with high affinity for HIV. Total lymphocyte count / TLC has been proposed as an alternative guide to CD4 in limited health facilities. This study aims to determine the correlation between Total Lymphocyte Count (TLC) and CD4 in HIV/AIDS patients in the W.Z. Johanne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…TLC has a strong positive correlation with CD4 count with a correlation coefficient of r = 0.767. Similar results were found in the study by Ola Wuan et al 26 involving 121 HIV patients in Kupang, a strong positive correlation was found between TLC and CD4 count (r = 0.799). 26 This finding is also supported by several studies showing that TLC can be a predictor of CD4 levels.…”
Section: Hiv Patients Characteristicssupporting
confidence: 90%
See 2 more Smart Citations
“…TLC has a strong positive correlation with CD4 count with a correlation coefficient of r = 0.767. Similar results were found in the study by Ola Wuan et al 26 involving 121 HIV patients in Kupang, a strong positive correlation was found between TLC and CD4 count (r = 0.799). 26 This finding is also supported by several studies showing that TLC can be a predictor of CD4 levels.…”
Section: Hiv Patients Characteristicssupporting
confidence: 90%
“…Similar results were found in the study by Ola Wuan et al 26 involving 121 HIV patients in Kupang, a strong positive correlation was found between TLC and CD4 count (r = 0.799). 26 This finding is also supported by several studies showing that TLC can be a predictor of CD4 levels. 27,28 The study conducted by Chen et al 26 showed that TLC <1570 cells/mm 3 could be a predictor of CD4 levels <350 cells/mm 3 with a sensitivity of 65% and a specificity of 80%.…”
Section: Hiv Patients Characteristicssupporting
confidence: 90%
See 1 more Smart Citation
“…4 When CD4 count is below 200 cells / µL, patient condition has entered the AIDS condition where opportunistic infections frequently occur. 5 There are opportunistic and neoplastic infections that may occur in HIV-infected patients, such as protozoan infections, fungal infections, bacterial infections, and viral infections. 6 Clinical manifestations that often appear in the oral cavity of HIV sufferers include oral candidiasis, periodontal disease, and disorders of salivary glands like xerostomia.…”
Section: Introductionmentioning
confidence: 99%